2010
DOI: 10.1159/000320609
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Effects of Bevacizumab-Based Treatment in Metastatic Colorectal Cancer

Abstract: Objective: The efficacy of bevacizumab in metastatic colorectal cancer (mCRC) could be related not only to its well-known antiangiogenetic properties but also to a hypothetical effect on the immune system of the host. Methods: We enrolled mCRC patients treated with a bevacizumab-based first-line therapy. Lymphocyte and dendritic cell subsets were evaluated at baseline, 3rd and 6th cycle. The clinical efficacy was estimated as response rate and progression-free survival. Forty healthy subjects were used as refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 38 publications
1
49
0
1
Order By: Relevance
“…Bevacizumab, a VEGF-specific antibody that is currently used for the treatment of metastatic cancers, reduces the percentage of circulating T reg cells in patients with colorectal carcinoma 154 , repletes B cell and T cell compartments in patients with metastatic colorectal cancer 155 , favours the differentiation of DCs 156 and facilitates tumour infiltration by lymphocytes 157 . Of note, it has recently been shown that cetuximab-coated EGFR-expressing colorectal carcinoma cells can be recognized by CD163 + macrophages, leading to the FcγR-dependent generation of membrane-bound (for example, PDL1) and soluble (for example, IL-10) immunosuppressive signals 158 .…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 99%
“…Bevacizumab, a VEGF-specific antibody that is currently used for the treatment of metastatic cancers, reduces the percentage of circulating T reg cells in patients with colorectal carcinoma 154 , repletes B cell and T cell compartments in patients with metastatic colorectal cancer 155 , favours the differentiation of DCs 156 and facilitates tumour infiltration by lymphocytes 157 . Of note, it has recently been shown that cetuximab-coated EGFR-expressing colorectal carcinoma cells can be recognized by CD163 + macrophages, leading to the FcγR-dependent generation of membrane-bound (for example, PDL1) and soluble (for example, IL-10) immunosuppressive signals 158 .…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 99%
“…The anti-VEGF therapy was able to revert the basal impairment of the majority of lymphocyte subsets, and it also showed a positive effect on mature T cells and T helper cells (related to the response to treatment) and on B lymphocytes (related to progression-free survival) [103]. [72] elegantly illustrates the theory (a) that dendritic cells modulate neovascularization by acting on existing vessels through the release of pro-and antiangiogenic factors.…”
Section: The Role Of the Dendritic Cells On Angiogenesis In Human Tumormentioning
confidence: 91%
“…We performed a prospective multicentric biologicalclinical trial in a selected patient population affected by metastatic colorectal cancer and suitable for first-line treatment containing bevacizumab to evaluate the influence of bevacizumab on the immune system and its correlation with clinical outcome [103]. Our mCRC population, despite a normal median leukocyte absolute number, showed a basal impairment of both B-and T-cell compartments, with a deficiency in NK cells.…”
Section: The Role Of the Dendritic Cells On Angiogenesis In Human Tumormentioning
confidence: 99%
“…The monoclonal antibody bevazumab targets it. It also increases tumor infiltrationby Tand B lymphocytes [15,16] and it is supposed to inhibit regulatory T cells (Treg cells) [17]. Bevacizumab got approved as first line treatment of metastatic breast cancer, as shown by clinical trials phase III patients who were HER2 negative and Miller et al showed in these patients bevacizumab with paclitaxel led to marked increase in PFS and objective response rate [18].…”
Section: Journal Of Gynecology Researchmentioning
confidence: 99%